Fish Wastewater and Fish Scale: A Corn Soil Enhancer (International Journal of Scientific Research and Management (IJSRM), 2023)
This study was conducted to determine the effects of fish waste water and fish scale as soil enhancer for the growth of sweet corn. The Experimental Research design with different treatments such as treatment 1 for 100% fish scale, treatment 2 for 100% fish waste water, treatment 3 for 50% fish scale and 50% fish water waste, and treatment 4 for commercialized fertilizer were employed for the growth of corn plants in terms of height, girth of stem, number of leaves and length of leaves. Mean and Post hoc analysis were used for the data analysis. It was found out that treatment 3 which was 50% fish scale and 50% fish water waste and treatment 4 which was commercialized fertilizer had the highest average growth of corn plants in all parameters. However, 100% fish scale and 100% fish water waste had the lowest average growth of corn plants in all parameters. Meanwhile, it was found out also that there was a highly significant difference in the effect of treatment 1 as contrasted among the other treatments of fertilizer. The same with treatment 2 as contrasted with treatment 3 and 4. However, the analysis found no significant difference on the effect of treatment 3 and 4 on the growth response of corn plants in all parameters.